Efecto del biochar a base de cáscara de cacao en la restauración de suelos erosionados en la zona rural, parroquia Calceta - Marcillo Vélez, Ana Patricia (2024)
This research aimed to evaluate the effect of organic amendments, compost and biochar from cocoa shell, on the physicochemical properties of the soil at the Olga Cobos site, Calceta, Bolívar canton. Initially, an analysis of the physicochemical conditions of the soil was carried out due to the presence of pedestals, furrows and little vegetation cover, obtaining an eroded soil as a derivation. Subsequently, a completely randomized block design (DBCA) was implemented with 4 treatments, 3 replications and 12 experimental units, varying the proportion of the amendments used. Once the treatments were completed, the physicochemical analysis was carried out again, which showed significant changes in the parameters pH, organic matter, porosity, apparent density and potassium in the different treatments. However, a reduction in humidity, phosphorus, electrical conductivity and nitrogen was observed. On the other hand, the execution of the analysis of variance (ANOVA) and the Tukey test indicated significant differences (p>0.05) between treatments T2, T3 and T4, especially in the parameters pH, electrical conductivity and potassium concentration. T4 standing out among the other treatments, as it contains a greater amount of organic amendment in relation to the others (40 g compost - 40 g biochar), thus supporting the alternative hypothesis proposed, because the treatments improved the physicochemical properties of the eroded soil.